Rare Isolated Jejunal Injury Following Blunt Abdominal Trauma - Anurag Roy; Arun Kumar M; Kshitij Jyoti; A Saravana Santhosh; Vitesh Popli (Journal of Acute Care Surgery)
Blunt trauma to the abdomen can result in various injuries which are potentially fatal if not promptly recognized and treated. Mechanism of injury, anatomical location, patient demographics, and clinical profile play crucial roles in diagnosis and management. The article presents 2 cases illustrating the challenges, and successful management of isolated jejunal injuries, and highlight the significance of early recognition and surgical intervention. These injuries are rare and there needs to be a high index of suspicion, especially in cases with atypical presentation. The cases in this article underscore the critical role of early surgical intervention in achieving optimal recovery and reducing the morbidity and mortality associated with isolated jejunal injuries. Clinicians need to consider the possibility of small bowel perforation following apparently trivial injuries, and employ a comprehensive approach to managing abdominal trauma.